The battle for iron in enteric infections. Issue 3 (11th August 2020) - Sousa Gerós, Ana; Simmons, Alison; Drakesmith, Hal; Aulicino, Anna; Frost, Joe N.
Summary: Iron is an essential element for almost all living organisms, but can be extremely toxic in high concentrations. All organisms must therefore employ homeostatic mechanisms to finely regulate iron uptake, usage and storage in the face of dynamic environmental conditions. The critical step in mammalian systemic iron homeostasis is the fine regulation of dietary iron absorption. However, as the gastrointestinal system is also home to >10 14 bacteria, all of which engage in their own programmes of iron homeostasis, the gut represents an anatomical location where the inter‐kingdom fight for iron is never‐ending. Here, we explore the molecular mechanisms of, and interactions between, host and bacterial iron homeostasis in the gastrointestinal tract. We first detail how mammalian systemic and cellular iron homeostasis influences gastrointestinal iron availability. We then focus on two important human pathogens, Salmonella and Clostridia ; despite their differences, they exemplify how a bacterial pathogen must navigate and exploit this web of iron homeostasis interactions to avoid host nutritional immunity and replicate successfully. We then reciprocally explore how iron availability interacts with the gastrointestinal microbiota, and the consequences of this on mammalian physiology and pathogen iron acquisition. Finally, we address how understanding the battle for iron in the gastrointestinal tract might inform clinical practice and inspire new treatments for important diseases. Abstract : Intestinal absorption of dietary iron is the key step regulating systemic iron homeostasis, but the human gut is also home to 100 trillion bacteria, which have their own, highly variable, iron requirements. Here, we explore molecular mechanisms underlying competition for this essential nutrient, focussing on salmonella, clostridia, and effects of iron acquisition on physiology during enteric infections. We discuss how understanding the battle for iron in the gut impacts on treatments for common intestinal inflammatory disorders.